Turkey’s Foreign Policy in South Caucasus and Interests of Iran and Russia - Heshmatollah Falahat Pishe; Vahid Sharbati; Mohammad Mehdi Mozafari (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2015)
With power succession of “ justice and development” party in Turkey in 2002 the foreign policy of this country in regional and far regional relations has seriously changed. Before 2000 Turkeys foreign policy was far westernized and the government policy-making was west, specially US, oriented. But with rise of justice and development government in Turkey, the country’s foreign policy changed to a multidimensional pragmatic interest-based policy .one aspect of this policy modified foreign policy toward collaboration with neighbors in order to enhance Turkey’s role in the region including south Caucasus. This study tries to evaluate Turkey foreign policy in Caucasus and its conflicting interests with the two powerful countries of area – Iran and Russia. The main question of this study is concentrated on the Turkey’s Caucasian Policy and its affects on interests of Iran and Russia. The hypothesis of the paper is that new Turkey’s foreign policy in the region brought contradiction between the country and two abovementioned powerful neighbors.